State of the Environment in Slum Area: A Case Study on Khora Slum, Khulna - Tanni, TT; Hasan, MJ; Azad, AK; Bakali, B (Journal of Environmental Science and Natural Resources, 2015)
The people fall in low income group is generally migrants and the local poor. Majority of slum people are living in poor quality housing where the absence of basic services and facilities is significant. The aim of the study is to evaluate the existing housing condition, to identify the present condition of sanitary facilities & drainage facilities, to evaluate the present condition of drinking water quality (lab analysis) & to determine the level of noise as this area is near to the main bus station & health services. To collect the required information random sampling method was used and questionnaire survey was done with slum dwellers. Lab analysis was made to find out the water quality. The noise level was measured using Noise Level meter. The study has tried to analyze the problem and advantages for living in the slum settlements, the slum settlements consequences on surroundings with a special reference of Khora Slum of Khulna City Corporation. The housing condition of the study area is not good. About 80% houses are in such a condition that it is very hard to live in there. The main problem is that these people are not aware of the environment where they are living as it is not their permanent living place. It was found that responsible authorities are not doing anything for the slum people. There is no qualified doctor in that area. Though the sadar hospital is nearer but they dont have enough money to go there. Mosquito is main problem here as there is no fixed place for throwing their household waste. Sanitation facilities are very poor here. There is only one community sanitary latrine with three chambers but it is not sufficient for all the people of the slum. Drinking water is another problem here as there exists only five tube wells of three are used by most of the people and the quality of water of the tube wells were analyzed in the lab. It was found that salinity level is very high (10 ppt) & color is dark of the water of the tube wells. By this study it will be easy to get the idea about house rent structure of the slums, getting services and facilities of the slums, distance of the services and facilities from the settlements, water supply and other utility services conditions of the slums. DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22187 J. Environ. Sci. & Natural Resources, 7(1): 295-304 2014